Emergency organization of public institutions in Nampula Province, Mozambique (Research, Society and Development, 2022)
The present work had as general objective to analyze the emergency organization measures in the face of fires that may occur in Public Institutions - Provincial Directorate of Culture and Tourism of Nampula, in Mozambique. The specific objectives were: To identify emergency management measures in the face of fires; Describe the basic procedures in emergency management in the face of fires in the Provincial Directorate of Culture and Tourism of Nampula, in Mozambique; To describe the impact of emergency management in the face of fires in the Provincial Directorate of Culture and Tourism of Nampula; Propose suggestive measures to improve emergency management in the face of fires. The methodological procedures of this work were based on the following types of research: qualitative, quantitative, descriptive, bibliographic and case study. Data were collected using an interview and a questionnaire that were aided by the observational technique. The study found that the level of emergency organization in the face of fires in public institutions is reasonable, as there are positive aspects within them, such as the existence of fire extinguishers, aeration of offices and also negative aspects such as lack of knowledge of emergency management by managers; lack of follow-up and monitoring of the deadlines established in the fire extinguishing devices; insufficiency of emergency exits; lack of signage for emergency exits; lack of evacuation alarm; lack of basic knowledge about the use of emergency equipment by the employees of the same institution.